Is Brics a Viable Solution for Russia in the Context of the Present Eu’s Economic Sanctions? - Ionescu, Romeo-Victor (Journal of Challenges, 2014)
The present political and military situation in Ukraine has an important impact on the regional and global economic connections. EU28 and USA imposed sanctions against Russia. The main objective of this paper is to quantify the potential economic changes in the world economic environment by analyzing the most significant global economic actors: EU28, USA, Russia and implicitly BRICS. The analysis in the paper has to components: a post factum analysis, using the latest official data (2013) and an ex antum analysis, which is supported by a forecast until 2020. The analysis conclusions are supported by pertinent statistic tables and diagrams. It is assisted by the IBM-SPSS software. The main conclusion of the analysis is that Russia is not able to cut the economic connections with EU28 and USA on short and average term. Moreover, BRICS is not a viable solution for Russia at the moment.